Praktikalitas Bahan Ajar Geometri Berbasis Modifikasi Model Project Based Learning (PjBL) “Kapal Nabi Nuh” untuk Mengembangkan Kemampuan Berpikir Kreatif Mahasiswa - Nasution, Eline Yanty Putri; Yulia, Putri (Institut Agama Islam Negeri Curup, 2024)
The available geometry teaching module at IAIN Kerinci still do not adequately accommodate students to discover material through scientific project tasks, and they are not yet integrated with Islamic values. The purpose of this research is to examine the practicality of geometry teaching materials based on modified Project Based Learning (PjBL)